SPIRITUAL INTELLIGENCE IN THE ISLAMIC EDUCATION CURRICULUM: EFFORTS TO COUNTER THE MORAL CRISIS OF GENERATION Z - Rifa Muslihatin Nufus; Nur Aisyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Generation Z grows up in a fast-paced and open digital era. On the one hand, they enjoy easy access to information and technology, but on the other hand, they also face a serious challenge in the form of a moral crisis. Phenomena such as a lack of responsibility, weakened empathy, and consumptive behavior often appear among young people. This study discusses the importance of spiritual intelligence in the Islamic Education (PAI) curriculum as an effort to address these issues. The method used is a literature review by examining various relevant sources. The findings show that spiritual intelligence helps students develop deeper religious awareness, self-control, and the ability to make wiser decisions. By integrating spiritual intelligence values into the PAI curriculum, it is expected that Generation Z will be better prepared to face the challenges of the modern era without losing their moral direction and character.